Sustainability and corporate governance an investigation on firm performance: A study on Malaysian public listed firms - Johl, S.K. (American Scientific Publishers, 2017)
This paper investigates whether embedding sustainability into corporate governance has affected firm performance of Malaysian listed companies. To achieve this goal we have analyzed the relationship between corporate governance and integrating sustainability indicators to examine whether there exist significant differences in performance. This study has used top 300 firms listed on Bursa Malaysia based on market capitalization. Earnings Per share (EPS) was used as proxies for firm performance. Also, reverse causation was controlled using firm size and leverage as exogenous variables for some of the corporate governance practices among the firms. The results revealed that there is a positive and significant relationship between sustainability and firm performance. © 2017 American Scientific Publishers All rights reserved.